2020
DOI: 10.1177/2732501620973029
|View full text |Cite
|
Sign up to set email alerts
|

Influenza as a Measure of Maternal Immune Activation and Its Effects on the Incidence of Encephalocele and Microtia

Abstract: Objective: Activation of the maternal immune (MIA) system while pregnant can have significant effects on fetal development. Here, the authors sought to examine MIA and its effects on fetal craniofacial formation. As a measure of MIA, data on maternal influenza infection was used, as influenza occurs in a predictive fashion, is not vertically transmitted, and is found to generate a robust maternal immune response. Thus, this study measures the association of the incidence of influenza infection in the United St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
2
1
Order By: Relevance
“…We speculate that certain pediatric tumors may follow similar trends, especially when considering potential effects of certain maternal environmental exposures. 24 However, in this study no clinically meaningful differences were found between geographical regions in the incidence of pediatric CNS tumors, either in aggregate or stratified by CNS tumor type.…”
Section: Discussioncontrasting
confidence: 67%
“…We speculate that certain pediatric tumors may follow similar trends, especially when considering potential effects of certain maternal environmental exposures. 24 However, in this study no clinically meaningful differences were found between geographical regions in the incidence of pediatric CNS tumors, either in aggregate or stratified by CNS tumor type.…”
Section: Discussioncontrasting
confidence: 67%
“…showed a strong correlation with influenza infection specifically during the 8th month of pregnancy with a very high odds ratio of 34.538 (95% confidence interval: 3.815-312.681), meaning that in month 8 of gestation, the odds of exposure to influenza in babies with encephalocele is 34.5 X the odds of no influenza exposure in babies with encephalocele. 9…”
Section: Correlation and Linear Regressionmentioning
confidence: 99%
“…YearFlu in FebruaryCS in March CS in April CS in May CS in June CS in July of pregnancy with a very high odds ratio of 34.538 (95% confidence interval: 3.815-312.681), meaning that in month 8 of gestation, the odds of exposure to influenza in babies with encephalocele is 34.5 X the odds of no influenza exposure in babies with encephalocele 9. Student's t-testAlso known as T-test, Student's t-test, developed by W. S. newborns in the U.S. with craniosynostosis in 2002 and the data from 2013 in the second column.…”
mentioning
confidence: 99%